Social Disadvantage and Education Experiences - Machin, Stephen (OECD Social, Employment and Migration Working Papers, 2006)
This paper discusses how social disadvantage affects the learning experiences of households with fewer economic resources, at each stage of the individuals' life-course, and on some of the "social" effects of such learning. It argues that while education can be an escalator out of social disadvantage - leading to better job prospects for youths facing greater risks of poverty and reducing the prevalence of income poverty in adult age - educational failure can reinforce it: a significant minority of students in several OECD countries do not even complete compulsory education; students' test scores in lower secondary education are strongly shaped by family characteristics; and the expansion of university education has most often benefited households with better educated parents. Far from "equalising" opportunities, education can be a powerful driver of social selection. When returns to education increase over time, this may lead to greater inter-generational persistence of poverty and less equality of opportunities